The crossfire of corporate real estate sustainable management (CRESM) with corporate triple bottom line objectives for office building / Nurul Sahida Fauzi ... [et al.] - Fauzi, Nurul Sahida; Zainuddin, Ashrof; Chuweni, Nor Nazihah; Johari, Noraini; Nawawi, Abdul Hadi (2021)
The emergence of corporations dabbling in sustainable real estate investment has caused a shift in the corporate real estate management (CRESM) field from the conventional way of managing a property to a more systematic approach involving high technology. The evolution is due to the need for sustainable buildings to comply with specific requirements to maintain their green certification while at the same time, ensure the success of the whole business operation. Many discussions mentioned that sustainable buildings give a positive impact to the business. However, most of these discussions did not specify which element of sustainable buildings significantly contributed to business performance and business goals. This research attempts to discover the relationship between CRESM and corporate sustainability (CS) objectives to determine the most significant element of CRESM that influences the overall business performance. A sustainable triple bottom line theory (TBL) has been used as a guide. A survey questionnaire was carried out involving 100 combinations of corporate real estate (CRE) managers, property managers, facility managers, operation managers, building managers, and financial managers that are directly involved in managing sustainable CRE. Data was then analysed using SPSS for descriptive statistics and Smart PLS for SEM. Results indicated six elements of CRESM are significantly affecting business performance. They are workspace management, energy management, innovation management, internal green management, workplace management and human satisfaction management.